Penyelesaian Sengketa Pemberian Ganti Kerugian Dalam Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum Atas Tanah Hak Guna Bangunan Diatas Hak Pengelolaan Dikaitkan Dengan Asas Kepastian Hukum - Santoso, Purwanto Budi; Fanciska, Wira; Atmadja, Dhody. AR. Widjaja (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Based on Article 33 paragraph 3 earth, water and Natural Resources under it are controlled by the state for the greatest prosperity of the people, from controlling the state issued various land rights. For the benefit of the nation, state and society the right to land can be revoked by providing appropriate compensation and in a manner regulated by law. 1 the problem to be examined in this thesis is how the dispute settlement compensation in the procurement of land for development for the public interest over land rights to building above the right of management and how the legal certainty, through the theory of legal certainty of Jan Michael Otto. The method used in this study is juridical-normative with the support of interviews, namely legal literature research with sources of primary, secondary and tertiary legal materials and with the support of interviews of several speakers. The research approach used is legislation approach, analytical approach, conceptual approach and legal material collection technique is done by identifying the literature of books, journals and other sources of legal materials. For technical analysis of legal materials is carried out by 1)grammatical interpretation, 2) systematic interpretation and analysis of data using quantitative. Based on the results of research with the object of land acquisition for the public interest HGB above HPL in Cilacap industrial estate and land procurement Jakarta-Bandung high speed rail project in Karawang concluded that the process of land acquisition has been held in accordance with procedures stipulated in Law No. 2 of 2012 and its derivatives, but there are still holders of HGB above HPL who feel dissatisfied and file objections and lawsuits so that disputes arise. This is because HGB holders on HPL do not fully understand the provisions stipulated in the legislation on land acquisition for development for the public interest. Among them are the objects of land acquisition that are given compensation and the sources used in determining the amount of compensation. Settlement of compensation disputes through deliberation cannot reach an agreement. Settlement through the court, the District Court and the Supreme Court provide a decision on the amount of compensation for the dispute in accordance with the results of the kjpp assessment. With the decision, the settlement of the dispute in question has also provided legal certainty for the community (the right party) to obtain their rights in accordance with the laws and regulations